The impact of work seeker support platforms on the development of South Africa's unemployed youth - Peinke, Simone (Graduate School of Business (GSB), 2023)
Youth unemployment remains an enduring and significant challenge in South Africa, with 43.2 % of people aged 15-34 and 59% aged 15-24 remaining unemployed, respectively. Similarly, economic discouragement among young people is on the rise. Micro-level barriers contribute significantly to the inability to access employment opportunities. These include the low skills levels of many young South Africans, the high costs of job-seeking, a lack of social capital, a lack of access to relevant job-seeker information, as well as the adverse mental health impacts of alienation, poverty and unemployment. With the rise of the Fourth Industrial Revolution and the rise of ICT for Development (ICT4D) interventions, several digital solutions have been developed in South Africa. These attempt to provide low-cost, scalable solutions to youth unemployment by addressing some of the barriers that young people experience. Despite the increased prevalence of such digital interventions, the degree to which they are capable of engaging and transforming the lives of the unemployed youth they target remains unclear. With increasing investments into 4IR interventions to address youth unemployment, closer examination is required. Accordingly, this study appraises one digital work seeker support platform in South Africa that provides skills matching and development opportunities to unemployed youth. The study focuses specifically on their experience of the platform. It uses post phenomenological constructs to analyse how young unemployed South Africans interpret the digital intervention and examines how these interpretations promote or inhibit their sense of agency and wellbeing. The findings suggest that digital youth employment interventions can inadvertently exacerbate some of the existing barriers, while also providing insight into how ICT4D interventions may be reimagined to address some of the factors that drive economic discouragement among young people.